PUEBI Update Socialization And Explanation For Elementary School Teachers in Magetan - Suharmono Kasiyun; Pance Mariati; Syamsul Ghufron (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2022)
The objectives of this Community Service are (1) to actively participate in improving the competence of teachers in Magetan Regency Elementary Schools; (2) Improving knowledge and mastery of Indonesian spelling based on Permendiknbud no. 50 of 2015 an elementary school teacher in Magetan Regency. (3) Improving the knowledge and skills of Indonesian elementary school teachers, Magetan Regency; (4) Improving the knowledge and writing skills of teachers at the Magetan Regency Elementary School. The specific targets to be achieved in this PKM are (1) increasing teachers' understanding of Indonesian Spelling based on Permendikbud No 50 of 2015; (2) Improving the knowledge and ability of teachers in writing scientific papers. Community service on the socialization of Indonesian Spelling based on Permendikbud No 50 of 2015 is based on an analysis of the situation that elementary school teachers in Magetan Regency still need to understand Indonesian Spelling material. The latest PUEBI socialization based on Permendiknas Number 50 of 20115 is the mastery of the Indonesian language, especially the latest Indonesian spelling. This Community Service activity has the following output targets. (1) Increased knowledge and linguistic insight of teachers to further increase the success of the teaching and learning process in the places where they teach (2) Increase the ability of teachers to write scientific papers in order to improve their careers.